0769 FDG-PET Imaging In Narcolepsy Type 1, Idiopathic Hypersomnia, And Non-Sleepy Controls. (27th May 2020) - Trotti, L; Meltzer, C; Rye, D; Nye, J
Abstract: Introduction: Functional imaging of narcolepsy type 1 (NT1) has shown disparate results, with evidence for both regional hyper- and hypo-metabolism. A FDG-PET study of idiopathic hypersomnia (IH) demonstrated regional hypermetabolism within the salience network. Methods: Patients with NT1 (n=14) or IH (n=16) were recruited, with age-matched, non-sleepy controls (HC, n=8). Patients discontinued treatment for ≥ 5 half-lives. Participants underwent injection of 18 F-fludeoxyglucose (FDG) in a dimly-lit room and were asked to remain awake, seated quietly. Simultaneous 6-channel EEG, EOG, and EMG were collected. Participants were alerted by a loud noise if sleep onset was observed. Thirty minutes after injection, patients underwent 36-minute PET scan. Images were spatially normalized to MPRAGE images and analyzed for group differences using SPM8. Results: Groups were similar in age (NT1: 30.0 (+/-SD 8.3), IH: 36.3 (+/-12.4), HC: 33.2 (+/-16.2), p=0.29) and gender (%women, NT1: 71%, IH: 87.5%, HC: 62.5%, p=0.37). Patients were sleepier than controls by Epworth (NT1: 18.2 (+/-3.5), IH: 15.8 (+/-3.2), HC: 5.0 (+/-2.7), p<0.0001) and MSLT mean latency (NT1: 2.0 (+/-1.4), IH: 5.1 (+/-1.7), HC: 14.6 (+/-2.6), p<0.0001). Despite attempts to remain awake, NT1 patients had difficulty maintaining wakefulness during uptake, obtaining 6.2 (+/-5.9) minutes sleep versus <1 minute for the other groups. Compared to controls, NT1 patients demonstrated increased activation in bilateral precentral gyri, left postcentral gyrus, left middle frontal gyrus, right insula, right inferior and superior temporal gyri, right fusiform gyrus, and bilateral inferior frontal gyri. Compared to controls, IH patients demonstrated increased activation in bilateral precuneus, bilateral inferior and middle frontal gyri, left middle and superior temporal gyri, left inferior parietal lobule, and left anterior cingulate. Conclusion: Different patterns of metabolic activity are seen in two hypersomnia disorders, implying disease-specific activity rather than non-specific sleepiness. Inadvertent sleep during uptake is more common in NT1. Support: K23 NS083748